Strain-specific properties of Lactobacillus plantarum for prevention of Salmonella infection. Issue 7 (29th June 2018) - Liu, Junsheng; Hu, Diangeng; Chen, Yingqi; Huang, Hongxuan; Zhang, Hao; Zhao, Jianxin; Gu, Zhennan; Chen, Wei
Abstract : Lactobacillus plantarum have strain-specific properties towards prevention of Salmonella infection. Abstract : Salmonella is a common food-borne pathogen; since lactobacilli show great potential for protecting against Salmonella infections, they are used as dietary supplements in functional foods. The aim of this study is to investigate the strain-specific properties and the involved mechanisms of action of Lactobacillus plantarum towards prevention of Salmonella infection. Mice were pretreated with mixed strains or single strain of Lactobacillus plantarum for 10 d prior to infection with Salmonella typhimurium SL1344, and the survival rates showed that lactobacilli exhibited strain-specific properties for preventing Salmonella infection. Then, in vitro and in vivo studies were carried out to investigate the involved mechanism of the strain-specific properties. The results showed that different Lactobacillus plantarum strains had different effects on inhibiting Salmonella growth, thus preventing adhesion to and invasion of epithelial cells by pathogens and enhancing immune responses. The present study demonstrated strain-specific properties of probiotics to prevent Salmonella infection and elucidated their underlying mechanisms.